Сакральність і сакралізація в середньополіських говірках чорнобильської зони. ІІ - Москаленко, Л.А. (Мовознавство, 2019)
У статті продовжено дослідження сакральних і сакралізованих елементів світосприймання, яке сформувалося в носіїв середньополіських говірок, що спрадавна органічно поєднували релігійність із елементами узвичаєної духовної культури.
Визначено дії, способи виконання дій, ознаки, слова, думки, звуки, темпоральні, локативні та квантитативні поняття, засвідчені в середньополіських говірках Чорнобильської зони як сакральні чи сакралізовані, простежено особливості їх номінації. З’ясовано специфіку взаємодії світського й сакрального, розглянуто процеси сакралізації. The article is devoted to the research on the repertoire of sacred and sacral actions
and ways of their execution, signs; words, thoughts, sounds; temporal, locative and
quantitative concepts, which was formed in the Chornobyl zone dialects, and to clarify the
peculiarities of their nomination.
On the material of the dialects of the Chernobyl zone, the carriers of which have long
been organically linked Christianity with elements of the traditional spiritual culture, the
actions and methods of their execution, signs; words, thoughts, sounds; temporal, local
and quantitative concepts, which are certified in these dialects as sacred or sacralized, as
well as the formation features of their repertoire have been traced.
The specifics of the interaction of the secular and the sacred has been found out, the
processes of sacralization and the nomination of sacred and sacral actions and ways of
their execution, signs have been considered, as well as words, thoughts, sounds; temporal,
locative, and quantitative concepts.